Picture-books: first structured reading materials for children (Libellarium: journal for research in the field of information and related sciences, 2012)
Early literacy has recently become a current topic, and there’s a widespread belief that literacy startsdeveloping almost as soon as the child is born, if the child is surrounded with adequate materials and persons who will motivate the development of literacy. The first structured reading materials that a child interacts with are picture-books. It is usually the first contact a child has with literature and a written word in general, and it happens during childhood, the child's most sensitive period, which is why it is important to pay special attention to the quality of picture-books. Croatian picture-books published till the early 80ies of the past century have been investigated to a some extent. However, the picture-books found on the Croatian market and in the libraries in the past 30 years have been the subject of research only sporadically. There's little data on the quality and features of this multifunctional material that is of such great importance for children.The aim of the paper is to give an overview of the relevant data found in literature on the historical development of picture-book publishing, their features, functions they help develop, their age-appropriateness, and quality. The paper presents research results stemming from the analysis of the Croatian Children's Book Centre documentation on contemporary picture-book publishing and data on the language of picture-books that are the result of a picture-book corpus study made as part of the PhD research by the author. The data on contemporary authors and illustrators was obtained by analysing the documentation of the Croatian Library Association, Commission for library services for children and youth. The language of the picture-book corpus was analysed using a computer programme, i.e. the analysis was conducted of the lexical diversity of picture-books for three-year olds. The picture-books have not been investigated from the linguistic perspective before, which makes this research innovative. The findings and results of this research can be applicable in picture-book publishing, first of all in changing the attitude of publishers, i.e. their approach to age-appropriateness and quality of picture-books.The aim of the paper is to give on overview of the picture-book situation, trying to raise awareness of the importance of their quality and potential, and spark off further picture-book research in different fields of arts and sciences. Thus, this paper will have an indirect practical value that may affect the current practice.
Keywords: picture-book; early literacy; historical development of picture-books; publishing; language